Antioxidant activity of essential oils from condiment plants and their effect on lactic cultures and pathogenic bacteria - Farias, Paula Karoline Soares; Lopes Silva, Júlio César Rodrigues [UNESP]; de Souza, Cintya Neves; da Fonseca, Francine Souza Alves; Brandi, Igor Viana; Martins, Ernane Ronie; Azevedo, Alcinei Mistico; de Almeida, Anna Christina (FapUNIFESP (SciELO), 2019)
Studies about preservative and antioxidant activity of essential oils have been encouraged in recent years, given their importance to food industry. The aim of the current study was to evaluate the antioxidant properties and antimicrobial activity of essential oils deriving from Syzygium aromaticum, Cymbopogon citratus and Lippia alba against lactic and pathogenic bacteria responsible for food-borne diseases. Essential oil antibacterial activity was assessed through disc diffusion and macrodilution tests conducted in a mixed lactic culture of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus (YF-L903) and of Escherichia coli (ATCC 8739), Staphylococcus aureus (ATCC 6538), Salmonella enterica (ATCC 6017) strains. Based on the chromatographic analysis results, the essential oils shown to be composed of eugenol (79.41%) which was the prevalent compound in S. aromaticum, geranial (31.89%), neral (24.52%) and β-myrcene (25.37%) in C. citratus, as well as of geranial (33.80%) and neral (25.63%) in L. alba. The observed antibacterial activity confirmed the dose-dependent effect of these three oils on all the assessed bacteria; there was halo inhibition at concentration 20μL mL -1 . The essential oil of S. aromaticum presented better antioxidant activity, with IC 50 equal to 5.76μg mL -1 and antioxidant activity index of 6.94, and it was considered strong (AAI>2.0) in comparison to the other evaluated oils. This essential oil also presented excellent antioxidant activity at concentrations lower than the one required to inhibit lactic cultures. Based in this outcome, the essential oil from S. aromaticum can be used as preservative agent in processed food whose formulation presents lactic cultures.
Atividade antioxidante do óleo essencial de plantas condimentares e efeito sobre culturas lácticas e bactérias patogênicas
Keywords: Capim cidreira; Clove; Lactic acid bacteria; Lemongrass; Probiotics